2010
DOI: 10.2147/dddt.s6591
|View full text |Cite
|
Sign up to set email alerts
|

Emerging treatments in the management of schizophrenia – focus on sertindole

Abstract: The antipsychotic treatment of schizophrenia is still marked by poor compliance, and drug discontinuation; the development of more effective and safer drugs still remains a challenge. Sertindole is a second-generation antipsychotic with high affinity for dopamine D2, serotonin 5-HT2A, 5-HT2C, and α1-adrenergic receptors, and low affinity for other receptors. Sertindole undergoes extensive hepatic metabolism by the cytochrome P450 isoenzymes CYP2D6 and CYP3A4 and has an elimination half-life of approximately th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Optimal outcomes of TDM require appropriate use of available analytical methods and basic knowledge, which must be amalgamated with the clinical situation of the patient, a complex joint effort of laboratory specialists, pharmacologists, pharmacists, treating physicians and the patient (4). Antipsychotic medication is the primary intervention for stabilization of acute psychotic episodes and prevention of recurrences and relapses in patients with schizophrenia (5). There are two groups of antipsychotic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal outcomes of TDM require appropriate use of available analytical methods and basic knowledge, which must be amalgamated with the clinical situation of the patient, a complex joint effort of laboratory specialists, pharmacologists, pharmacists, treating physicians and the patient (4). Antipsychotic medication is the primary intervention for stabilization of acute psychotic episodes and prevention of recurrences and relapses in patients with schizophrenia (5). There are two groups of antipsychotic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Sertindole, a second-generation antipsychotic, was introduced in Europe in 1996 [8]. It rapidly became associated with sudden cardiac deaths and an in vitro study demonstrated that sertindole has high affinity as an antagonist of the cardiac potassium channel [9].…”
Section: Introductionmentioning
confidence: 99%